PERUBAHAN ADAT PERKAWINAN PADA MASYARAKAT TRANSMIGRAN BALI DI DESA MORINI MULYA KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - I Putu Hardiana s; Asmarita Asmarita (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2018)
This study focuses on the causes of changes in the customary marriage of Balinese transmigrants in Morini Mulya Village, Landono District, Konawe Selatan Regency. It uses a theory of cultural acculturation. This study uses ethnographic methods. The data collection techniques are observation and in-depth interviews. The results show that there is a change in the customary marriage to the Balinese transmigrant community in Morini Mulya Village. Some aspects of this change include: (1) changes in the order of customary marriage processions, which appear to have been different from the processions carried out by the people in Bali (their place of origin); (2) changes in equipment and food used in the marriage procession; (3) the occurrence of marriage between different castes and different religions. The three main things that cause this change are (1) because they are in a transmigration area that is much different from the conditions in the area of origin; (2) because of the weak customs that can be maintained by transmigrant communities, and (3) economic factors. Keywords: customary, marriage, changes, transmigrants.